Health of migrants, refugees and asylum seekers in detention in Tripoli, Libya, 2018-2019: Retrospective analysis of routine medical programme data. - Anna Kuehne (Public Library of Science (PLoS), 2021)
Libya is a major transit and destination country for international migration. UN agencies estimates 571,464 migrants, refugees and asylum seekers in Libya in 2021; among these, 3,934 people are held in detention. We aimed to describe morbidities and water, hygiene, and sanitation (WHS) conditions in detention in Tripoli, Libya. We conducted a retrospective analysis of data collected between July 2018 and December 2019, as part of routine monitoring within an Médecins Sans Frontières (MSF) project providing healthcare and WHS support for migrants, refugees and asylum seekers in some of the official detention centres (DC) in Tripoli. MSF had access to 1,630 detainees in eight different DCs on average per month. Only one DC was accessible to MSF every single month. The size of wall openings permitting cell ventilation failed to meet minimum standards in all DCs. Minimum standards for floor space, availability of water, toilets and showers were frequently not met. The most frequent diseases were acute respiratory tract infections (26.9%; 6,775/25,135), musculoskeletal diseases (24.1%; 6,058/25,135), skin diseases (14.1%; 3,538/25,135) and heartburn and reflux (10.0%; 2,502/25,135). Additionally, MSF recorded 190 cases of violence-induced wounds and 55 cases of sexual and gender-based violence. During an exhaustive nutrition screening in one DC, linear regression showed a reduction in mid-upper arm circumference (MUAC) of 2.5mm per month in detention (95%-CI 1.3-3.7, p<0.001). Detention of men, women and children continues to take place in Tripoli. Living conditions failed to meet minimum requirements. Health problems diagnosed at MSF consultations reflect the living conditions and consist largely of diseases related to overcrowding, lack of water and ventilation, and poor diet. Furthermore, every month that people stay in detention increases their risk of malnutrition. The documented living conditions and health problems call for an end of detention and better protection of migrants, refugees and asylum seekers in Libya.